The Missionary Movement Of Tuan Guru Bajang (TGB) In West Nusa Tenggara - Mulyadin; Muliaty Amin; Sattu Alang; Firdaus; Mirwan; Murdifin (Gudang Jurnal Multidisiplin Ilmu, 2025)
This study discusses the missionary movement of Tuan Guru Bajang (TGB) in West Nusa Tenggara. This is a qualitative study. The research design is field research. The results of this study indicate that: Tuan Guru Bajang (TGB) Zainul Majdi, as a preacher, possesses exceptional competence and academic qualifications. His approach to delivering his sermons is calm and approachable, making his messages easily accepted by people from all walks of life. The target audience of TGB Zainul Majdi's preaching encompasses all segments of society, including those of different religious backgrounds. During his tenure as governor, TGB continued to fulfil his duties as a preacher.